Effectiveness of the OSSRBA (Online Single Submission Risk Based Approach) System in Business Licensing Services in Payakumbuh City DPMPTSP - Zahara, Anisa; Kabullah, Muhammad Ichsan; Putera, Roni Ekha; Putra, Roni Ekha (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
OSS RBA is a digital-based application that is used as a means of issuing licensing documents for community business activities. The problem behind this research is that the OSS RBA system cannot be implemented optimally due to limitations in both the application, service providers, and the public when using OSS RBA. Research objective: to determine the effectiveness of the RBA OSS system in business licensing services at the Payakumbuh City Investment and One-Stop Integrated Services Service. Research method: descriptive with a qualitative approach. Using the theory of e-government effectiveness by Timothy Dolan, namely the Six-Dimensional Assessment Tool (6 DAT), Results/Findings: The results of this research indicate that the OSS RBA system in Payakumbuh City is still not effective. Several indicators have been met, such as a good security system, an integrated database, and application updates. However, there are still shortcomings that can be seen from the limited means of communication, lack of information regarding coordination between parties involved in the OSS RBA, low understanding of technical OPD regarding the verification process, interactivity that is still limited, the performance of government licensing services that is not yet visible, and public feedback in providing assessments on the licensing process for the OSS RBA system that is not yet available. This causes the use of the OSS RBA system in society to be not optimal, so the OSS RBA system is still at a transition stage from the old method to the new method.